Global population stabilisation policy and declining work-age population: a threat to global economic sustainability. (4th November 2019) - Alam, Md. Mahmudul; Murad, Md. Wahid; Molla, Rafiqul Islam; Rahman, Khondaker Mizanur; Khondaker, Taslima Rahman
Faced with an exponentially growing world population, what is required is a population stabilisation policy to control the global fertility rates. This has implications for the working-age population in the future, and lead to a serious economic crisis. It is envisaged that by the year 2050 the work-age population will have seriously declined, but is still expected to look after an increasing dependent population. This paper argues that to maintain sustainable economic growth, and to support the associated technological advances in the future there will be demand for a larger labour force. It notes that the industrialised countries are now managing with migrant populations drawn mostly from high fertility but low-income countries. In the global context this is only a zero-sum game without increasing the stock of the world's actual total labour force. Therefore, the world population needs to increase to meet the growing demand for a larger labour force in order to achieve economic sustainability. Since the earth's population carrying capacity largely depends on advanced technology functioning well, to support society's lifestyle expectations, the world should not defer planned population growth.